The Influence of Entrepreneurial Education and Entrepreneurial Skills on Entrepreneurial Intentions through the Internship Program as an Intervening Variable for Vocational School Students in Banyuwangi Regency - Baldan, Najimul; Hermawan, Agus; Makaryanawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research entrepreneurial knowledge through educational curricula, entrepreneurial learning, and practical experience via internship programs. The quality of these programs is key, as better internship experiences positively affect both entrepreneurial learning and skills. Consequently, an integrated approach that combines effective entrepreneurship education, practical skills development, and impactful internship experiences is recommended. In conclusion, this research provides valuable insights into the dynamics of entrepreneurship education, skills development, and internship experiences in shaping the entrepreneurial intentions of vocational school students. The results offer a basis for refining entrepreneurship curricula and designing more effective internship programs, contributing to the broader goal of nurturing a robust entrepreneurial ecosystem in Indonesia.